FLOUTING CONVERSATIONAL MAXIMS IN THE ROM-COM MOVIE “THE KISSING BOOTH 2” - Dohans, Western (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2024)
The purpose of this study are to analyze the types of flouting maxims found in The Kissing Booth 2 Movie and to identify the reasons behind the flouting maxim since it is very important in order to make the communication as effective as possible. In this study, the researcher used a theory proposed by Grice in Levinson (1983) in analyzing the types of flouting maxim and the theory proposed by Leech (1983) in analyzing the reason behind the flouting maxim occurs in the movie. This study used descriptive qualitative method to provide a deeper understanding regarding to the flouting maxim and the reasons of flouting. The data were collected from the conversation that occurred among the characters in The Kissing Booth 2 Movie. The data were collected through observation and note- taking techniques. The study concludes that the flouting maxim of quantity is mostly applied and the most type of the reason behind the flouting maxim is collaborative reason.